Exploring the Potential for Electricity Trade and Interconnection among Yemen and GCC Countries - World Bank (Washington, DC, 2012)
This report has been prepared by Economic Consulting Associates (ECA) under contract to the World Bank to explore the potential for interconnection and electricity trade among Yemen and the countries of the Gulf Cooperation Council (GCC). The primary objective for this study is to identify the efficient scenarios to utilize gas and electricity resources through cross-border integration among Yemen and the GCC countries. The analysis includes an assessment of gas resources available for the electricity systems and identification of the potential for cross-border interconnections and integration among the respective countries to identify efficient, ways to utilize the gas resources and generation capacities from national and regional perspectives. The key findings of the study are as follows: a) reform of natural gas pricing policies in the GCC countries would encourage the development of gas resources and discourage the use of gas for energy intensive export industries, petrochemicals, aluminum, etc. This will release natural gas for power generation and could release some gas for export either to GCC neighbors or to the rest of the world; and b) there are no benefits to interconnecting Yemen and Saudi Arabia's networks for trade in bulk electricity. Yemen's power system is too unreliable at present to be considered for reserve sharing as a member of the GCC interconnection scheme. Investigation of the Yemen-Saudi interconnection should therefore be postponed.